Epidemiology of leptospirosis in Colombia between 2007 and 2015 - Clara S. Arias Monsalve; Daniela Salas Botero; Maria Rita Donalisio (Universidad de Antioquia, 2021)
Leptospirosis is a zoonotic disease of global distribution caused by the bacterium Leptospira. In Colombia, it has been mandatory to report this disease since 2007. Objective: to perform an epidemiological analysis of human leptospirosis in Colombia at the national, departmental and municipal levels for the period between January 2007 and December 2015. Methods: A retrospective ecological study of the temporal trend and spatial distribution of leptospirosis cases reported between January 2007 and December 2015 was conducted. The variables of sex, age, municipality of residence, area of residence (urban, rural), date of onset of symptoms, and lethality were analyzed. Results: A total of 23,994 suspected cases were reported, of which 39.51% were confirmed; 82.4% came from urban areas; 68.87% presented in men; the lethality was 2.66% in men and 2.04% in women. The departments with the highest number of cases were Valle del Cauca (n=2032), Antioquia (n=1747), Atlántico (n=1159); the incidence varied between 2 (Arauca) and 465.4 (Guaviare) per 100,000 inhabitants. At the municipal level, Cali had the highest number of cases (n=682), followed by Barranquilla (n=612) and San José del Guaviare (n=448). The highest incidence was 1597.6 in Pueblo Rico (Risaralda), followed by Sabanas de San Ángel (Magdalena) with 883.4 and San José del Guaviare (Guaviare) with 742.5; the majority of municipalities had incidences between 0 and 50 per 100,000 inhabitants. Conclusions: Leptospirosis is distributed throughout Colombia with 85% of the cases concentrated in 10 of its 32 departments. At the municipal level there is a large degree of variation in annual incidences. Six hotspots for cases were also identified, indicating that there are areas of high risk for the disease.